High-resolution outgoing longwave radiation dataset from Kalpana-1 satellite during 2004-2012 - Mahakur, M.; Prabhu, A.; Sharma, A. K.; Rao, V. R.; Senroy, S.; Singh, Randhir; Goswami, B. N. (Current Science, 2013)
Long record of high-resolution quality-controlled outgoing longwave radiation (OLR) from geostationary platforms like Kalpana-1 has the potential not only to provide detailed information of cloud types contributing to the measure of rain, but also helps unravel convective cloud organization in the tropics from small scale to meso- and synoptic scales. A research quality product of three hourly OLR for the period May 2004 June 2012 is produced from Kalpana-1 very high resolution radiometer (VHRR) radiances over the Indian region (40 degrees S-40 degrees N, 25-125 degrees E) in a regular grid of 0.25 x 0.25 degrees. The quality and usefulness of the dataset is demonstrated here using some illustrative examples. Although these data are available for a relatively short-period, it is shown that they will be potentially more useful than the widely used OLR from NOAA satellites in representing the annual cycles, particularly over the desert and humid oceans, due to their frequent sampling and quality. The active-break periods in the Indian summer monsoon picked up by both the OLR match well. This three hourly OLR estimated from Kalpana-1 VHRR is able to describe the fine-scale structure of the diurnal variation over the region.
Keywords: Active break periods; diurnal variation; geostationary platforms; outgoing longwave radiation

Nickel and cobalt affect galactosylation of recombinant IgG expressed in CHO cells. - Prabhu, A.; Gadgil, M. (BioMetals, 2019)
Glycosylation is an important product quality attribute of antibody biopharmaceuticals. It involves enzymatic addition of oligosaccharides on proteins by sequential action of glycosyltransferases and glycosidases in the endoplasmic reticulum and golgi. Some of these enzymes like galactosyltransferase and N-acetylglucosaminyltransferase-I require trace metal cofactors. Variations in trace metal availability during production can thus affect glycosylation of recombinant glycoproteins such as monoclonal antibodies. Variability in trace metal concentrations can be introduced at multiple stages during production such as due to impurities in raw materials for culture medium and leachables from bioreactors. Knowledge of the effect of various trace metals on glycosylation can help in root-cause analysis of unintended variability in glycosylation. In this study, we investigated the effect of nickel and cobalt on glycosylation of recombinant IgG expressed in Chinese hamster ovary cells. Nickel concentrations below 500 µM did not affect glycosylation, but above 500 µM it significantly decreases galactosylation of IgG. Cobalt at 50 µM concentration causes slight increase in G1F glycans (mono galactosylated) as previously reported. However, higher concentrations result in a small increase in G0F (non galactosylated) glycans. This effect of nickel and cobalt on galactosylation of recombinant IgG can be reversed by supplementation of uridine and galactose which are precursors to UDP-Galactose, a substrate for the enzymatic galactosylation reaction.
Keywords: cobalt; Galactosylation; glycosylation; Nickel; Process variability; Trace metals